REPRESENTASI PIKTORIAL TUNANETRA TIDAK SEJAK LAHIR BERDASARKAN MODEL PEMROSESAN INFORMASI: Pictorial Representation Of Blind People Not From Birth Based On Information Processing Model - Mutmainah, Siti; Siswono, Tatag Yuli Eko; Abadi, Abadi (Universitas Tadulako, 2024)
This study used a 14-year-old male student whose criteria were not to be blind from birth without any other defects. A hard blow to the head back is caused the student's disability. Pupils with disabilities no longer attend regular primary school from IV class onwards. This study aims to determine the process of pictorial representation of right triangles based on information processing models. This type of research is descriptive and explorative with a qualitative approach. This study uses the main instrument and the supporting instruments. Here, students are asked to perform mathematic assignments and then interviewed, and all activities performed are analyzed using observation sheets. Data analysis was performed with three activities: data condensation, data presentation, and conclusion and verification. The results of the study show that blind students can make pictorial representations. Creating images can be seen in students' activities in completing mathematical assignments. Information or external stimuli enter the sensory register through the senses of hearing and touch, after which attention and perception arise. Perception by retrieving the necessary concepts from long-term memory. When retrieving process, students experience moments of forgetting, and then they repeat the parts of a right-angled triangle until they finally have a correct right-angled triangle.